Structure of papers and Nonwovens - Pereira, Mário José Teixeira (2010)
We characterise the structure of fibrous materials: papers and nonwovens by diffraction and transmission of light. This allows the measurement of the fibres orientation distribution of the sample as a whole or for the surfaces using replicas. Applications of the methods are demonstrated in the case of paper for the control of the curl tendency and for two kinds of nonwoven materials, one used in the tailoring of surgical garments and the other used as components of the baby diapers.